Δ53Cr values of catchment runoff exhibit seasonality regardless of bedrock Cr concentrations: Role of periodically changing chromium export fluxes. Issue 12 (17th December 2021) - Andronikov, Alexandre V.; Novak, Martin; Kram, Pavel; Sebek, Ondrej; Andronikova, Irina E.; Stepanova, Marketa; Vitkova, Hyacinta; Antalova, Elena; Komarek, Arnost
Abstract: One pre‐requisite for the construction of a global chromium isotope mass balance is detailed understanding of Cr isotope systematics in the critical zone where redox‐processes can modify the isotope signature of geogenic Cr input into the hydrosphere. A Cr isotope inventory of bedrock, soil, and runoff was performed in a Central European headwater catchment underlain by amphibolite, situated in the vicinity of two previously studied catchments underlain by different bedrock types (serpentinite and leucogranite). Fresh bedrock in the amphibolite catchment NAZ contained 300 mg/kg Cr, serpentinite at PLB contained 800 mg/kg Cr, and leucogranite at LYS contained 2 mg/kg Cr. Monthly hydrochemical monitoring at all three sites revealed higher Cr(VI) export fluxes in winter than in summer. NAZ was characterized by a distinct seasonality in the δ 53 Cr values, with minima during winter/spring snowmelts (−0.35‰) and maxima during dry summers (0.40‰). Similar seasonality in δ 53 Cr values had been reported from PLB and LYS. Bedrock at all three sites had similar Cr isotope composition close to −0.10‰, a value indistinguishable from the δ 53 Cr value of bulk silicate Earth (BSE). Positive mean δ 53 Cr value of NAZ runoff indicated Cr‐isotope fractionations during weathering of geogenic Cr(III), combined with adsorption of the resulting Cr(VI) on soil particles during pedogenesis. However, the mass‐weighted mean δ 53 Cr of NAZ runoff was lower (−0.08‰), indistinguishable from the Cr isotope signature of bedrock. The same pattern of lower mass‐weighted mean δ 53 Cr values of runoff, compared to arithmetic mean δ 53 Cr values of runoff, were observed also at PLB and LYS. We suggest that elevated Cr runoff fluxes in winter remove some of the residual isotopically light Cr that accumulated in the soil during summer. Seasonality in runoff δ 53 Cr values appears to be a relatively widespread phenomenon, de‐coupled from Cr availability for chemical weathering. Abstract : In three small‐forested catchments from contrasting crystalline bedrock, seasonality in δ 53 Cr values of runoff was observed. In summer, when export fluxes of Cr are relatively low, the δ 53 Cr values of runoff tend to be higher than in winter when export fluxes of Cr are relatively high. Seasonality in runoff δ 53 Cr values appears to be a general phenomenon, de‐coupled from Cr availability for weathering.